Rapid tilted-plane Gerchberg-Saxton algorithm for holographic optical tweezers - Cai, Yanan; Yan, Shaohui; Wang, Zhaojun; Li, Runze; Liang, Yansheng; Zhou, Yuan; Li, Xing; Yu, Xianghua; Lei, Ming; Yao, Baoli (Optics express, 2020)
Benefitting from the development of commercial spatial light modulator (SLM), holographic optical tweezers (HOT) have emerged as a powerful tool for life science, material science and particle physics. The calculation of computer-generated holograms (CGH) for generating multi-focus arrays plays a key role in HOT for trapping of a bunch of particles in parallel. To realize dynamic 3D manipulation, we propose a new tilted-plane GS algorithm for fast generation of multiple foci. The multi-focal spots with a uniformity of 99% can be generated in a tilted plane. The computation time for a CGH with 512×512 pixels is less than 0.1 second. We demonstrated the power of the algorithm by simultaneously trapping and rotating silica beads with a 7×7 spots array in three dimensions. The presented algorithm is expected as a powerful kernel of HOT.